1987
DOI: 10.1111/j.0954-6820.1987.tb03358.x
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Study of the Influence of Continuous Subcutaneous Insulin Infusion Treatment on Diabetic Retinopathy during Pregnancy

Abstract: ABSTRACT. Laatikainen L, Teramo K, Hieta‐Heikurainen H, Koivisto V, Pelkonen R (Department of Ophthalmology, I and II Departments of Obstetrics and Gynaecology, III Department of Medicine, Helsinki University Hospital, Helsinki, Finland). A controlled study of the influence of continuous subcutaneous insulin infusion treatment on diabetic retinopathy during pregnancy. Forty consecutive pregnant patients with insulin‐dependent (Type I) diabetes mellitus were randomized at the end of the first trimester for tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Progression of retinopathy has been noted in those pregnancies where there was a rapid decrease in HbA 1c by some authors who have cautioned against achieving euglycaemia too rapidly. 3,6,7,26 Therefore, cautious normalization of serum glucose in patients with poor glycaemic control and retinopathy is advisable. 7,8,27,28 The Diabetes in Early Pregnancy Study found that duration of diabetes mellitus of more than 15 years in a patient was an important risk factor in the progression to severe retinopathy in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Progression of retinopathy has been noted in those pregnancies where there was a rapid decrease in HbA 1c by some authors who have cautioned against achieving euglycaemia too rapidly. 3,6,7,26 Therefore, cautious normalization of serum glucose in patients with poor glycaemic control and retinopathy is advisable. 7,8,27,28 The Diabetes in Early Pregnancy Study found that duration of diabetes mellitus of more than 15 years in a patient was an important risk factor in the progression to severe retinopathy in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Good glycaemic control is the cornerstone for both maternal and foetal wellbeing during pregnancy. Worsening of DR has been correlated with the degree of improvement of glycemic control obtained with the institution of intensive therapy performed before and during pregnancy [129,130,131,132].…”
Section: Metabolic Factorsmentioning
confidence: 99%
“…Secondly, cotton wool spots (CWSs), areas of infarction of the nerve fibre layer of the retina, are associated with low fasting blood sugar [87] and rapidly achieved strict metabolic control [130,147]. These spots develop in some type I diabetic women with BDR during advancing pregnancy.…”
Section: Natural Course Of Dr During Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…However, by maintaining normoglycemia, regression of the proliferative retinopathy was achieved without laser therapy during the following months (Rosenlund et al 1988). Laatikainen et al (1987), Puklin et al (1982), Lawson et al (1982) and van Ballegooie et al (1984) reported on patients with an increasing proliferative change to retinal vessels in diabetic retinopathy despite optimal blood glucose control by the insulin pump. These patients showed no early stage of the retinopathy prior to insulin pump therapy.…”
Section: Proliferative Retinopathy Despite Normoglycemiamentioning
confidence: 99%